Peranan Hukum Islam, Demokrasi dan Hak Asasi Manusia dalam Kehidupan Bernegara - Halim, Abdul (LP3M STITNU AL HIKMAH MOJOKERTO, 2023)
Islam has rules that are like laws, and one of them is called the Al-Quran. Democracy means treating people fairly and equally, letting them be part of making decisions, and following the laws. Some words that are related to democracy are equality, freedom, and human rights. These are also important in Islam and are followed in every country.